The Relationship between Work – Family Conflict and Identity Crisis - maryam rezaei dareh deh; morad baradaran; gholamhossein karami (توسعه اجتماعی, 2016)
This research investigated the relationship between both work-family conflict and women's identity crisis. For explaining the research's issue is used of the Identity theory and role theory Peter Burke's Identity Control Theory, and particularly emphasis on Peter Burke's Identity Control theory and scarcity role approach. The survey method and questionnaire is used, in this study. Statistical population is all employed women in Khorram Abad city. Using the formula of Cochran was selected using cluster sampling 310 people in three occupational groups of women, and was questioned. Data analysis is both descriptive statistics inferential statistics and using of the compare mean, and regression analysis to investigate the relationship between independent variables and the dependent variable and test research hypotheses. Findings indicated that between roles syndicate work-family and work-family conflict experience is established (exists) a relationship Significant and positive and further changes of the conflict explains the family factor and family role expectations. Between family social support of employed and work-family conflict experience is established (exists) a relationship Significant and negative. Finally, research findings indicated that was confirmed a relationship Significant and positive between the work- family conflict experience and women's identity crisis.